2005
DOI: 10.1016/j.orthres.2004.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Rat supraspinatus muscle atrophy after tendon detachment

Abstract: Rotator cuff tears are one of the most common tendon disorders found in the healthy population. Tendon tears not only affect the biomechanical properties of the tendon, but can also lead to debilitation of the muscles attached to the damaged tendons. The changes that occur in the muscle after tendon detachment are not well understood. A rat rotator cuff model was utilized to determine the time course of changes that occur in the supraspinatus muscle after tendon detachment. It was hypothesized that the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
1
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 33 publications
7
107
1
14
Order By: Relevance
“…This finding argues against formation of new fibers with increased tension and removal of fibers with decreased tension, but supports re-establishing the baseline composition, and is consistent with prior studies [5,48]. Our resultant hypertrophied Type IIa and Type IIb fibers appear to run counter to the studies previously mentioned, where muscle demonstrates hypertrophy of slow fibers and a decrease in fast glycolytic fiber content when subjected to increased load [12,14,16,49].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding argues against formation of new fibers with increased tension and removal of fibers with decreased tension, but supports re-establishing the baseline composition, and is consistent with prior studies [5,48]. Our resultant hypertrophied Type IIa and Type IIb fibers appear to run counter to the studies previously mentioned, where muscle demonstrates hypertrophy of slow fibers and a decrease in fast glycolytic fiber content when subjected to increased load [12,14,16,49].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, simply acutely dissecting extra-muscular connective tissue results in reduced muscle force output [47]. Subsequent to our experiment, it was shown that rat supraspinatus muscle, when simply tenotomized at its humeral insertion, returns to its pre-surgical mass and muscle size when allowed a 16 week recovery [48]. These findings support our "splinting" assertion.…”
Section: Discussionsupporting
confidence: 80%
“…6,24,25 The term ''infiltration'' conveys a sense of permeation of lipids into muscle. As we showed in this in vitro study, myoblasts can trans-differentiate to PPARg expressing adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle preparations with more than 15% damage were eliminated from the study. Fiber area analysis was achieved using immunohistochemistry and an antibody recognizing laminin as previously described (13). The imaging software provided further confirmation that the fibers were no cut obliquely during sectioning.…”
Section: Methodsmentioning
confidence: 99%